Efficacy of Tamsulosin in Relieving Double-J Stentrelated Symptoms: a Randomized Controlled Study - Thakur, Deepak K; Chapagain, Suman; Luitel, Bhojraj; Chalise, Pawan Raj; Sharma, Uttam Kumar; Gyawali, Prem Raj (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Ureteral stent placement is an increasingly common procedure in urological practice. They are used for both prevention and treatment of ureteral obstruction. Despite improved design and materials, many patients still develop stent-related symptoms which commonly affect quality of life and sometimes necessitate early removal. Tamsulosin improves stent-related symptoms and quality of life. But such study has not been conducted in Nepalese context. In the present study, the effect of Tamsulosin in improving double-J stent-related symptoms and quality of life following ureteral stent placement was studied. Methods: This study was carried out in the Department of Urology and Kidney Transplant Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal from February 2015 to January 2016. Forty six patients were included in the study and randomized into Tamsulosin (T) group and Control (C) group each having 23 patients. In addition to standard postoperative care, Tamsulosin group received 0.4 mg Tamsulosin daily for 2 weeks and Paracetamol on demand and control group received only Paracetamol (1gram/dose). Stent related symptoms and quality of life was assessed by International prostate symptom score (IPSS) at discharge (day2) and at the time of DJ stent removal (2 weeks). Pain was evaluated by visual analog scale (VAS) and analgesic requirement was documented. Data were analysed using Statistical Package for the Social Sciences (SPSS) 20, chisquare test and Student’s t- test was used. A p-value of <0.05 was considered significant. Results: Mean age in Tamsulosin group was 37.96±12.98 years and Control group 36.43± 10.99 years (p=0.67).There was no significant difference in IPSS (p=0.141), QoL index (p=0.089) and VAS (p=0.59) in the two groups at the time of discharge. At the time of DJ stent removal, IPSS (p<0.001), QoL index(p<0.001), VAS(p=0.004) and analgesic needed(p<0.001) was significantly lower in T group than in C group. Conclusion: Tamsulosin lowers stent related symptoms, pain and improves quality of life in patients with indwelling DJ stent though the effect is not immediate.